Reconstructing long‐term human impacts on plant communities: an ecological approach based on lake sediment DNA. Issue 7 (April 2015) - Pansu, Johan; Giguet‐Covex, Charline; Ficetola, Gentile Francesco; Gielly, Ludovic; Boyer, Frédéric; Zinger, Lucie; Arnaud, Fabien; Poulenard, Jérôme; Taberlet, Pierre; Choler, Philippe
Abstract: Paleoenvironmental studies are essential to understand biodiversity changes over long timescales and to assess the relative importance of anthropogenic and environmental factors. Sedimentary ancient DNA ( sed aDNA) is an emerging tool in the field of paleoecology and has proven to be a complementary approach to the use of pollen and macroremains for investigating past community changes. Sed aDNA‐based reconstructions of ancient environments often rely on indicator taxa or expert knowledge, but quantitative ecological analyses might provide more objective information. Here, we analysed sed aDNA to investigate plant community trajectories in the catchment of a high‐elevation lake in the Alps over the last 6400 years. We combined data on past and present plant species assemblages along with sedimentological and geochemical records to assess the relative impact of human activities through pastoralism, and abiotic factors (temperature and soil evolution). Over the last 6400 years, we identified significant variation in plant communities, mostly related to soil evolution and pastoral activities. An abrupt vegetational change corresponding to the establishment of an agropastoral landscape was detected during the Late Holocene, approximately 4500 years ago, with the replacement of mountain forests and tall‐herb communities by heathlands and grazed lands. Our results highlight the importance of anthropogenic activities in mountain areas for the long‐term evolution of local plant assemblages. Sed aDNA data, associated with other paleoenvironmental proxies and present plant assemblages, appear to be a relevant tool for reconstruction of plant cover history. Their integration, in conjunction with classical tools, offers interesting perspectives for a better understanding of long‐term ecosystem dynamics under the influence of human‐induced and environmental drivers.